Impact of hybrid PET/MR technology on multiparametric imaging and treatment response assessment of cervix cancer. Issue 3 (December 2017) - Daniel, Michaela; Andrzejewski, Piotr; Sturdza, Alina; Majercakova, Katarina; Baltzer, Pascal; Pinker, Katja; Wadsak, Wolfgang; Mitterhauser, Markus; Pötter, Richard; Georg, Petra; Helbich, Thomas; Georg, Dietmar
Abstract: Background and purpose: Multimodal tissue characterization by combined MRI and PET has high clinical potential in the context of sub-target definition for dose painting and response assessment but its clinical exploration is yet limited. The aim of this study was to prove the potential and feasibility of hybrid PET/MRI to non-invasively measure tumor hypoxia, perfusion and microstructure at one stop in tumors of the uterine cervix during chemoradiotherapy. Material and methods: Ten cervix cancer patients were subjected to simultaneous multiparametric PET/MRI with [ 18 F]fluoromisonidazole ([ 18 F]FMISO). Imaging was scheduled before, twice during and after chemoradiotherapy. Intra- and inter-time point analyses of the extracted parameters (i.e. ADC, K trans, ABrix, [ 18 F]FMISO-tumor to background ratio (TBR)) were performed. The [ 18 F]FMISO uptake- and ADC-spatio-temporal changes were assessed. Results: Patient averaged ADC values increased from baseline to follow up (1.03 ± 0.11/1.30 ± 0.13 × 10 −3  mm 2 /s), while the TBR decreased (1.73 ± 0.24/1.36 ± 0.19), K trans dropped over time (0.17 ± 0.05/0.05 ± 0.05 min −1 ); for all above p  < 0.05. None of these parameters correlated significantly on a voxel-by-voxel basis. Low-ADC regions spatially varied over time. There was pronounced reduction of the [ 18 F]FMISO-avid volumes during treatment. Conclusions: The suggested hybrid PET/MRI protocol to non-invasively investigate tumor hypoxia, perfusion and microstructure at one stop was feasible, revealing spatio-temporal response patterns that could be utilized for comprehensive sub-target definition for dose painting and response assessment.